FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Tambunan, Lydia Septaria; Santioso, Linda (Jurnal Paradigma Akuntansi, 2025)
This research aims at how the effect of intellectual capital, firm size, liquidity, leverage toward financial performance on manufacturing industry listed on the Indonesia Stock Exchange during 2018-2020. Sample was selected using purposive sampling method and the valid data was 213 data sample. Data processing techniques using multiple regression analysis what helped by Eviews program (Econometric Views) for Windows version 12 and Microsoft Excel 2019. The results of this study indicate that intellectual capital have a positive significant influence on financial performance, firm size and leverage have a negative significant influence on financial performance, and liquidity does not have a significant and negative influence on financial performance. The implication of this study is to be an input for companies in improving financial performance and for investors in seeing whether or not the company's financial performance is good to be funded.